Effective Biomarkers for Proof-of-Concept - Suhara, Tetsuya; Kodaka, Fumitoshi (Current Medical Imaging, 2008)
Effective biomarkers have been desired both for diagnostic purposes and for the evaluation of the effects of drugs. Positron emission tomography allows the visualization of several components of neurotransmissions, such as receptors and transporters. In vivo neuroimaging including neuroreceptor imaging and enzyme activity imaging has contributed to drug evaluation in terms of 1) rational drug dosing, 2) biodistribution of drug, 3) therapeutic rationale for drug use, and 4) mechanism of drug action [1]. In this article, we focused on the rational drug dosing of antipsychotic drugs and antidepressants using receptor occupancy and proof-of-concept of drugs, as well as new therapeutic methods for Alzheimer disease.
Keywords: Biomarker